Scale : Discourse and Dimensions of Social Life - Lempert, Michael; Carr, E. Summerson, 1969- (Book collections on Project MUSE., 2016)
"Wherever we turn, we see diverse things scaled for us, from cities to economies to history to love. We know scale by many names, and through many familiar antinomies: 'local' and 'global, ' 'micro' and 'macro, ' 'events' and the 'longue duree.' Even the most critical amongst us often proceed with our analysis as if such scales are the readymade platforms of social life, rather than asking how, why, and to what effect scalar distinctions are forged in the first place? How do scalar distinctions help actors and analysts alike make sense of and navigate their social worlds? What do they reveal and what do they conceal? How are scales construed and what effects do they have on the way the people who abide by them think and act? This path-breaking volume attends to the practical labor of scale making and the communicative practices this labor requires. Ethnographically, the chapters demonstrate that scale is practice and process before it is product, whether in the work of projecting 'the commons, ' claiming access to 'the big picture, ' or scaling the seriousness of a crime"--Provided by publisher.